A single‐switch equalization charger using multiple stacked buck‐boost converters for series‐connected energy‐storage modules. Issue 3 (25th November 2012) - Uno, Masatoshi; Tanaka, Koji
Abstract Series connections of energy‐storage modules such as electric double‐layer capacitors (EDLCs) and lithium‐ion batteries result in voltage imbalance because of the nonuniform properties of individual modules. Conventional voltage equalizers based on traditional DC‐DC converters require numerous switches and/or transformers, and therefore their costs and complexity tend to increase. This paper proposes a novel single‐switch equalization charger using multiple stacked buck‐boost converters. The single‐switch operation not only reduces the circuit complexity but also contributes to increasing the reliability. The fundamental operating principles and design procedures of key components are presented in detail. An experimental charge test using a 25‐W prototype of the proposed equalization charger was performed for four series‐connected EDLC modules whose initial voltages were intentionally imbalanced. The experimental results demonstrated that the proposed equalization charger could charge the series‐connected modules preferentially in the order of increasing module voltage and that all the modules could be charged up to a uniform voltage level. © 2012 Wiley Periodicals, Inc. Electr Eng Jpn, 182(3): 57–67, 2013; Published online in Wiley Online Library (wileyonlinelibrary.com). DOI 10.1002/eej.22332